New species and new record of cavernicolous ground beetles from Sichuan Province, China (Coleoptera: Carabidae: Pterostichini and Platynini) - Tian, Mingyi; He, Li (Zootaxa, 2020)
Two new species of cave-adapted ground beetles are described and illustrated from Sichuan Province, southwestern China: Jujiroa zhouchaoi sp. nov. from the calcareous conglomerate cave Shenxian Dong in Mt. Zhaogong (Dujiangyan, Chengdu) and Pterostichus (Huaius) hanwang sp. nov. from the limestone cave Hanwang Dong (Chaotian, Guangyuan). A new locality for Jujiroa deliciola Uéno and Kishimoto, 2001 is given. Keys to species of the genus Jujiroa Uéno, 1952 and the subgenus Huaius Tian and Huang, 2019 (in Tian et al. 2019) are also provided.